Self-repairing type warm-mixing flame-retardant microcapsule and asphalt mixture
By introducing nano-silica particles with surface-grafted azophenyl groups and an organic wax-montmorillonite composite component into microcapsules, a multi-component synergistic mechanism was constructed, which solved the shortcomings of microcapsule materials in terms of functional synergy, durability and release regulation, and improved the performance of asphalt pavement.
Patent Information
- Application Number
- CN202511023530.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-28
AI Technical Summary
Existing microencapsulated materials have shortcomings in terms of functional synergy, durability, and release regulation, resulting in poor performance improvement of asphalt pavement.
By introducing nano-silica particles with surface-grafted azophenyl groups and an organic wax-montmorillonite composite component, a triple triggering mechanism of light, mild stress, and heat is constructed to achieve the synergistic effect of warm mixing, self-healing, and flame-retardant components, and to precisely control the release of the core material.
It improves repair efficiency and flame retardant durability, achieves efficient functional coupling, and optimizes road surface performance.
Smart Images

Figure CN120838308A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of traffic engineering, and in particular to a self-healing warm-mix flame-retardant microcapsule and asphalt mixture. Background Technology
[0002] In the field of transportation engineering, multifunctional microcapsule technology is widely used to improve the performance of asphalt pavements, especially the integration of self-healing, warm mix and flame retardant functions.
[0003] However, existing microcapsule materials generally suffer from the core problem of insufficient functional synergy, which is manifested in the following aspects: (1) Weak synergistic effect between components: the warm-stirred functional components and the self-healing and flame-retardant components usually act independently, not only lacking a mutual promotion mechanism, but also potentially causing performance antagonism due to physical or chemical incompatibility; (2) Poor functional durability: the flame-retardant components often cannot continue to play a role after the microcapsule breaks down, and the self-healing process lacks a long-term catalytic mechanism, resulting in insufficient material durability; (3) Coarse release regulation: the release rate and location of the core material are difficult to control precisely, resulting in waste of repair materials or insufficient repair in key areas, affecting the overall performance improvement effect.
[0004] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the present invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a self-healing warm-mix flame-retardant microcapsule and asphalt mixture. Through multi-component synergy, a triple triggering mechanism of light, temperature, and stress is constructed to precisely control the release of the core material. The warm-mix, self-healing, and flame-retardant components promote each other, improving repair efficiency and flame-retardant durability, achieving efficient functional coupling, and optimizing pavement performance.
[0006] The first objective of this invention is to provide a self-healing warm-mix flame-retardant microcapsule, the microcapsule comprising a core material and a shell material; the core material comprises a self-healing component and a warm-mix functional component in a mass ratio of 2-4:6-8, the self-healing component being at least one of sulfur, epoxy resin or recycled asphalt, and the warm-mix functional component being an organic wax-montmorillonite composite component, wherein the montmorillonite is modified by a silane coupling agent.
[0007] The shell material is at least one of ammonium polyphosphate, melamine-formaldehyde resin or nano aluminum hydroxide, and the surface of the shell material is loaded with nano silica particles with surface-grafted azophenyl groups.
[0008] This invention introduces nano-silica particles grafted with azophenyl groups and an organic wax-montmorillonite composite component. The photoresponsive cis-trans isomerism of the azophenyl groups can drive changes in the spatial arrangement of the nano-silica particles through intermolecular forces. This change can indirectly promote the exfoliation and dispersion of montmorillonite sheets in the organic wax-montmorillonite composite component. When the microcapsule shell breaks, the micro-stress generated by the photo-induced azophenyl isomerism can break the aggregation state of the montmorillonite sheets, making them more uniformly dispersed in the repair area, while enhancing the contact efficiency with the self-healing component and accelerating the curing reaction. On the other hand, montmorillonite is coupled with a silane coupling agent. After modification, its surface organic groups can form weak interactions with azophenyl groups. This interfacial interaction can guide the montmorillonite to migrate directionally to the crack interface during the core material release process. Combined with the reinforcing effect of nano-silica particles on the shell material, it not only improves the mechanical strength of the repaired area, but also enhances the local flame retardant effect through the synergistic effect of montmorillonite and the flame retardant components of the shell material. Furthermore, the layered structure of montmorillonite and nano-silica particles can form a physical interwoven network. While controlling the release rate of the core material, the release behavior can be controlled by light and temperature through the photoresponsive characteristics of azophenyl, making the synergy of self-healing and temperature-stirring functions more precise and efficient.
[0009] As a preferred embodiment of the present invention, the preparation method of the organic wax-montmorillonite composite component includes:
[0010] In step S1, montmorillonite is added to an ethanol solution of silane coupling agent with a mass fraction of 5-8%, and the mass ratio of montmorillonite to silane coupling agent is 10-8:1. After heating and stirring, centrifugation, washing, drying, grinding and sieving are performed to obtain modified montmorillonite. In this step, the surface of montmorillonite is modified by silane coupling agent to graft organic groups onto its surface, which significantly improves the compatibility and dispersibility of montmorillonite with organic waxes, laying the foundation for the subsequent formation of a stable organic wax-montmorillonite composite system.
[0011] S2 involves heating and melting the organic wax at 120–140°C, then adding modified montmorillonite at a mass ratio of 5–3:1 (organic wax to modified montmorillonite). After stirring and reacting for 1–2 hours, heating is stopped, and stirring continues until the temperature drops to 60–70°C. After cooling, the mixture is pulverized and sieved. In this step, the modified montmorillonite is uniformly dispersed in the molten organic wax to form a composite system with a layered structure and an interpenetrating wax matrix network. This structure retains the warm-stirring function of the organic wax and enhances the thermal stability and structural strength of the composite component through the physical barrier effect of the montmorillonite layers.
[0012] As a preferred embodiment of the present invention, the method of adding modified montmorillonite includes:
[0013] First, lower the temperature to 100-110℃, then add the modified montmorillonite in 2-6 portions, with an interval of 15-20 minutes between each addition. After each addition, increase the stirring speed by 50-100 r / min. After all the montmorillonite has been added, raise the temperature back to 120-130℃.
[0014] In the above method, not only can the uniform dispersion of modified montmorillonite in organic wax be promoted through stepwise temperature control and gradient speed-increasing stirring, but the local contraction and expansion of organic wax molecular chains can also be induced by temperature changes, making it easier for montmorillonite sheets to embed into the wax lattice and form a stable wax-earth interpenetrating structure. This structure enhances the temperature-stirring stability of the composite components on the one hand, and makes the interlayer spacing of montmorillonite more easily regulated by temperature stimulation during the subsequent release of the core material on the other hand. It forms a cross-stimulus synergy with the photoresponse characteristics of nano-silica particles grafted with azophenyl groups in the shell material. The azophenyl isomer stress induced by light can be transferred to the core material through the shell material, causing the interpenetrating structure to dissociate rapidly and release active sites, accelerating the curing reaction with the self-healing components, thus forming a unique multi-component synergistic mechanism in terms of temperature stirring, dispersion and repair efficiency.
[0015] As a preferred embodiment of the present invention, a method for preparing nano-silica with surface-grafted azophenyl groups includes:
[0016] Q1 involves soaking nano-silica particles in hydrochloric acid solution, filtering, washing to neutral, and then drying. In this step, impurities (such as residual silicates and organic residues) adsorbed on the particle surface are removed by acidic conditions, while surface hydroxyl groups are activated. After filtering, washing to neutral, and drying, the reactivity of nano-silica with subsequent silane coupling agent derivatives can be improved, providing a clean surface rich in reaction sites for subsequent grafting reactions.
[0017] Q2: 4-hydroxyazobenzene and 3-isocyanatepropyltriethoxysilane are added to toluene at a molar ratio of 1:1.1-1.2. The mixture is heated and stirred under nitrogen protection to obtain a silane coupling agent derivative containing an azophenyl group. After cooling, it is ready for use. In this step, the hydroxyl group (-OH) of 4-hydroxyazobenzene undergoes a nucleophilic addition reaction with the isocyanate group (-NCO) of 3-isocyanatepropyltriethoxysilane to form a carbamate bond (-NH-COO-). The azophenyl group is covalently grafted onto the silane coupling agent molecule to form a silane coupling agent derivative containing an azophenyl group. Nitrogen protection can prevent the isocyanate group from being decomposed by water in the air, ensuring that the reaction proceeds in a directional manner.
[0018] Q3. The pretreated nano-silica particles are added to a mixed solvent of anhydrous ethanol and toluene and ultrasonically dispersed. Then, a silane coupling agent derivative is added, wherein the mass ratio of nano-silica to silane coupling agent derivative is 10-8:1. The mixture is refluxed and stirred at 80-90℃ for 6-8 hours. In this step, the silanol groups (Si-OH) on the surface of the pretreated nano-silica undergo a hydrolysis-condensation reaction with the ethoxy groups (-OC2H5) in the silane coupling agent derivative to generate siloxane bonds (Si-O-Si), which allow the azophenyl groups to be covalently grafted onto the surface of the nano-silica. The mixed solvent of anhydrous ethanol and toluene provides a suitable polar environment for the reaction. Ultrasonic dispersion ensures that the nano-silica is uniformly suspended. Refluxing and stirring at 80-90℃ promotes the complete condensation reaction.
[0019] Q4 The mixture is centrifuged, and the resulting solid is washed with anhydrous ethanol and dried to obtain nano-silica particles with azophenyl groups grafted on the surface. In this step, centrifugation separates the grafted product from the unreacted silane coupling agent derivative, washing with anhydrous ethanol removes the residual free derivative, and vacuum drying removes the solvent.
[0020] As a preferred embodiment of the present invention, the loading of nano-silica with surface-grafted azophenyl groups is 5 to 15% of the total mass of the shell material.
[0021] The above ratio ensures uniform distribution of the azobenzene on the shell surface, fully utilizes the photoresponse characteristics of azobenzene to precisely control the release of the core material, and enhances the mechanical strength of the shell through the reinforcing effect of nano-silica. At the same time, it avoids particle agglomeration due to excessive load or excessive load, so that the shell material achieves a balance between mechanical properties, photoresponse sensitivity and flame retardant component compatibility, providing a stable foundation for the synergistic effect of multiple components.
[0022] As a preferred embodiment of the present invention, the microcapsule particle size is 20-80 μm.
[0023] The above-mentioned size range is suitable for the gradation gap of asphalt mixtures, which can ensure that the core material has sufficient loading to perform self-healing and warm-mix functions, while avoiding the pavement strength reduction caused by excessive particle size affecting aggregate interlocking. At the same time, this particle size is conducive to the uniform dispersion of microcapsules in the mixture, and can accurately respond to stress and release the core material when cracks occur, taking into account both functional efficiency and structural stability.
[0024] As a preferred embodiment of the present invention, the mass ratio of the core material to the shell material is 1:0.6 to 1.5.
[0025] The aforementioned ratio range ensures that the core material has sufficient space to accommodate the self-healing and warm-mix functional components, guaranteeing the release of sufficient material after the shell ruptures to achieve efficient repair and warm-mixing effects. Simultaneously, the appropriate shell mass ratio forms a stable encapsulation structure, maintaining the integrity of the microcapsules, preventing core material leakage during storage, and enabling it to withstand external stresses during road service. This ensures timely rupture and release of the core material, achieving a good balance between storage stability, functional release efficiency, and shell protective performance.
[0026] A second objective of this invention is to provide a method for preparing the above-mentioned self-healing warm-stir flame-retardant microcapsules, comprising:
[0027] In step T1, the self-healing component and the warm-stirring functional component are melt-mixed at 60–80°C to obtain a liquid core material. In this step, the self-healing component and the warm-stirring functional component form a uniformly dispersed core material system, ensuring that the self-healing component and the warm-stirring functional component work synergistically in the subsequent microcapsule preparation and service process, laying the foundation for the core material to quickly exert its self-healing and warm-stirring functions after release.
[0028] T2 disperses the shell material and nano-silica particles with azophenyl groups grafted onto their surfaces in deionized water to form an aqueous solution. This step provides a continuous phase for the subsequent emulsification process and ensures that the nano-silica particles are evenly distributed in the aqueous phase, creating conditions for their subsequent loading onto the shell material surface and ensuring the synergistic effect between the shell material and the functional particles.
[0029] T3 mixes the liquid core material with an aqueous solution and shears-emulsifies it to form an oil-in-water emulsion.
[0030] In step T4, an initiator is added to the emulsion, the pH is adjusted to 3-5, and the temperature is raised to 70-90℃ for in-situ polymerization for 2-4 hours. After freeze-drying and sieving, microcapsules are obtained. In this step, the monomers in the shell material undergo condensation reaction under acidic conditions and 70-90℃ under the action of the initiator, forming a three-dimensional network structure through covalent cross-linking, which gradually coats the surface of the core material droplets to form the microcapsule shell material. The nano-silica particles with azophenyl groups grafted on the surface are embedded in the shell material network through physical adsorption or chemical bonding, realizing the loading of nano-silica particles on the shell material surface, and endowing the shell material with photoresponsiveness and mechanical reinforcement properties.
[0031] As a preferred embodiment of the present invention, the initiator is ammonium persulfate or azobisisobutyronitrile, and the amount added is 0.5-2% of the shell material weight.
[0032] Ammonium persulfate, as a water-soluble initiator, can decompose in aqueous solution to generate free radicals, which can initiate the condensation reaction of the shell material monomers, and is especially suitable for polymerization processes in aqueous environment; azobisisobutyronitrile, as an oil-soluble initiator, can provide free radicals near the oil phase interface to promote the directional polymerization of the shell material on the surface of the core material droplets.
[0033] An addition of 0.5% to 2% ensures sufficient free radical concentration to drive the polymerization reaction efficiently, avoiding incomplete polymerization and loose structure of the shell material due to insufficient initiator, while also preventing excessive initiator residue from affecting the stability of the shell material or the performance of the core material. This results in a dense and appropriately strong encapsulation structure, balancing polymerization efficiency and overall microcapsule performance.
[0034] The third objective of this invention is to provide an asphalt mixture comprising, by weight parts: 4-6 parts asphalt, 85-92 parts aggregate, 6-8 parts mineral powder, and 0.5-1.0 parts microcapsules.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention introduces nano-silica particles with surface-grafted azophenyl groups and an organic wax-montmorillonite composite component. The photoresponsive cis-trans isomerism of the azophenyl groups can drive the spatial arrangement of nano-silica particles through intermolecular forces. This change can indirectly promote the peeling and dispersion of montmorillonite sheets in the organic wax-montmorillonite composite component. When the microcapsule shell breaks, the small stress generated by the azophenyl isomerism induced by light can break the aggregation state of the montmorillonite sheets, making them more evenly dispersed in the repair area, while enhancing the contact efficiency with the self-healing component and accelerating the curing reaction.
[0036] After being modified with a silane coupling agent, montmorillonite's surface organic groups can form weak interactions with azophenyl groups. This interfacial interaction can guide the montmorillonite to migrate directionally to the crack interface during the core material release process. Combined with the reinforcing effect of nano-silica particles on the shell material, it not only improves the mechanical strength of the repaired area, but also enhances the local flame retardant effect through the synergistic effect of montmorillonite and the flame retardant components of the shell material. Furthermore, the layered structure of montmorillonite and nano-silica particles can form a physically interwoven network. While controlling the core material release rate, the release behavior can be regulated by both light and temperature by taking advantage of the photoresponsive characteristics of azophenyl, making the synergy between self-healing and temperature-stirring functions more precise and efficient. Attached Figure Description
[0037] Figure 1 This is a flowchart of the preparation method of the self-healing warm-stirring flame-retardant microcapsules of the present invention. Detailed Implementation
[0038] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0039] The sources of raw materials in the specific implementation are as follows:
[0040] Table 1: Sources of raw materials in specific implementation methods
[0041]
[0042]
[0043] Example 1
[0044] The preparation method of self-healing warm-stir flame-retardant microcapsules includes the following steps:
[0045] 1. Preparation of modified montmorillonite
[0046] Raw materials: 100g sodium montmorillonite, 12g silane coupling agent (KH550), 500mL 6% ethanol solution.
[0047] Procedure: Add sodium-based montmorillonite to the above ethanol solution, heat and stir at 60°C for 3 hours (stirring rate 300 r / min), then centrifuge (4000 r / min, 10 min), wash three times with anhydrous ethanol, vacuum dry at 80°C for 4 hours, grind through a 200-mesh sieve to obtain modified montmorillonite.
[0048] 2. Preparation of organic wax-montmorillonite composite component (warm-mix functional component)
[0049] Raw materials: 200g organic wax (polyethylene wax, melting point 125℃), 50g modified montmorillonite prepared in step 1.
[0050] Procedure: Melt the organic wax at 130℃, cool it to 105℃, and add the modified montmorillonite in three portions (15 min apart, stirring at 400 r / min for the first time, 500 r / min for the second time, and 600 r / min for the third time). After all the wax has been added, heat it to 125℃ and continue stirring for 1.5 h. Then stop heating and stir until the temperature drops to 65℃. After cooling, pulverize the wax through a 100-mesh sieve to obtain the organic wax-montmorillonite composite component.
[0051] 3. Preparation of nano-silica particles with surface grafted azophenyl groups
[0052] Raw materials: 90g of nano-silica (50nm particle size), 300mL of hydrochloric acid solution (5% by mass), 10g of 4-hydroxyazobenzene, 12g of 3-isocyanate propyltriethoxysilane, 200mL of toluene, and 400mL of anhydrous ethanol and toluene mixed solvent (volume ratio 1:1).
[0053] operate:
[0054] ① Soak nano-silica in hydrochloric acid solution for 2 hours, filter, wash with deionized water until neutral, and dry at 60℃ for 3 hours;
[0055] ② Add 4-hydroxyazobenzene and 3-isocyanate propyltriethoxysilane to toluene, stir at 70°C for 2 hours under nitrogen protection to obtain silane coupling agent derivative;
[0056] ③ Add the pretreated nano-silica to the mixed solvent, ultrasonically disperse for 30 min (power 300W), add the silane coupling agent derivative, and reflux and stir at 85℃ for 7 h;
[0057] ④ Centrifuge (5000 r / min, 15 min), wash three times with anhydrous ethanol, and vacuum dry at 60℃ for 6 h to obtain the target particles.
[0058] 4. Preparation of liquid core material
[0059] Raw materials: 30g of self-healing component (sulfur), 70g of the warm-stirring functional component prepared in step 2.
[0060] Procedure: Add both to a container, heat to 70°C to melt, and stir for 30 minutes (at a rate of 500 r / min) to obtain a homogeneous liquid core material.
[0061] 5. Preparation of Aqueous Solutions
[0062] Raw materials: shell material (80g melamine-formaldehyde resin prepolymer + 20g ammonium polyphosphate), 10g of azobenzene-grafted nano-silica prepared in step 3 (accounting for 10% of the total mass of the shell material), and 500mL deionized water.
[0063] Procedure: Add the shell material and nano-silica to deionized water and stir for 20 minutes (speed 600 r / min) to form an aqueous suspension.
[0064] 6. Preparation of oil-in-water emulsions
[0065] Procedure: Mix the liquid core material (100g) from step 4 with the aqueous solution from step 5, and shear at 3000r / min for 15min in a high-speed shear emulsifier to form an oil-in-water emulsion (oil phase droplet size 20-80μm).
[0066] 7. In-situ polymerization and microcapsule preparation
[0067] Raw materials: 1g initiator (ammonium persulfate) (1% of the shell material weight), hydrochloric acid.
[0068] Procedure: Add ammonium persulfate to the emulsion, adjust the pH to 4 with hydrochloric acid, heat to 80℃, and stir for 3 hours (400 r / min). After the reaction is complete, freeze-dry the product at -40℃ for 24 hours, and sieve (300 mesh) to obtain self-healing warm-stirred flame-retardant microcapsules with a particle size of 30-60 μm.
[0069] Example 2
[0070] The self-healing component (sulfur) in Example 1 was replaced with epoxy resin.
[0071] Example 3
[0072] The self-healing component (sulfur) in Example 1 was replaced with recycled bitumen.
[0073] Comparative Example 1
[0074] The preparation method of the organic wax-montmorillonite composite component in Example 1 is modified to the following steps, and the rest is the same as in Example 1;
[0075] The organic wax was heated and melted at 130°C, and the temperature was maintained at 130°C. 50g of modified montmorillonite was added all at once, and the mixture was immediately stirred at 600r / min for 1.5h. Heating was stopped and the mixture was stirred until the temperature dropped to 65°C. After cooling, the mixture was pulverized and passed through a 100-mesh sieve to obtain the organic wax-montmorillonite composite component.
[0076] Comparative Example 2
[0077] Unlike Example 1, the montmorillonite in the organic wax-montmorillonite composite component was not modified with a silane coupling agent.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that the nano-silica particles with surface-grafted azophenyl groups are replaced with nano-silica particles.
[0080] The self-healing warm-mix flame-retardant microcapsules prepared in the examples and comparative examples were applied to asphalt mixtures. By mass, the mixture consisted of 5 parts asphalt, 88 parts aggregate (basalt, particle size 5-10 mm), 7 parts mineral powder (limestone powder), and 0.8 parts microcapsules.
[0081] Procedure: Heat the aggregate to 160°C, add microcapsules and asphalt (melted at 150°C), stir for 5 minutes, then add mineral powder (preheated at 150°C), and continue stirring for 3 minutes to obtain asphalt mixture.
[0082] The above asphalt mixture was subjected to the following tests, and the results are shown in Table 2.
[0083] (1) Self-repair efficiency
[0084] Test method:
[0085] Prepare asphalt mixture specimens containing microcapsules (e.g., 50mm×50mm×50mm), and test their initial compressive strength (according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" T0713).
[0086] A three-point bending method was used to pre-create cracks in the middle of the specimens (approximately 1 / 3 of the specimen height). The specimens were divided into two groups: one group was subjected to 365nm ultraviolet light (power 10mW / cm²). 2 Irradiate for 30 minutes, and another group is left to rest naturally for the same amount of time;
[0087] After 24 hours of curing, the compressive strength of the two groups of specimens was tested again, and the self-healing efficiency was calculated as "repaired strength / initial strength × 100%".
[0088] (2) Limiting Oxygen Index (LOI) of the remediation area
[0089] Test method:
[0090] Samples (100mm×10mm×4mm) containing the repaired crack area were cut from the repaired asphalt mixture specimen and operated according to GB / T2406.2 "Test for Burning Performance of Plastics - Oxygen Index Method";
[0091] The sample is fixed in an oxygen index meter, the flow rate of the oxygen-nitrogen mixed gas is adjusted, and the minimum oxygen concentration that just sustains the combustion of the sample is measured. This is the LOI value of the repaired area.
[0092] (3) Low-temperature crack resistance of the repaired pavement
[0093] Test method:
[0094] Take the repaired asphalt mixture specimen (300mm×300mm×50mm), simulate the actual working conditions of the road surface, and conduct a low-temperature bending test according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" T0729;
[0095] The specimen was kept at -10℃ for 4 hours, and then loaded at a rate of 50 mm / min using a three-point bending device. The maximum bending tensile strain and bending tensile strength at the fracture point were recorded.
[0096] Table 2: Test Results of Examples and Comparative Examples
[0097]
[0098] In the embodiments, modified montmorillonite and organic wax are uniformly dispersed through stepwise addition and gradient stirring to ensure stable warm-mixing function; the nano-silica grafted with azobenzene not only enhances the mechanical properties of the shell material, but its azophenyl groups can also undergo configurational changes under ultraviolet light, promoting the release of the core material from the shell material. Combined with the self-healing activity of sulfur, it significantly improves the repair efficiency under light irradiation; the ammonium polyphosphate in the shell material forms a flame-retardant synergistic system with montmorillonite, improving the limiting oxygen index; the core material has good compatibility with asphalt, and the microcapsules are uniformly dispersed, reducing low-temperature stress concentration, thus exhibiting excellent low-temperature flexural strength and strain performance.
[0099] Comparative Example 1 changed the preparation of the organic wax-montmorillonite composite component to a one-time addition of montmorillonite at high temperature and high speed stirring, which resulted in severe agglomeration of montmorillonite, which could not be uniformly combined with organic wax, and the stability of the warm-mix function decreased; the warm-mix component in the core material was unevenly dispersed, and it was difficult to form a continuous repair interface when the self-healing component was released, so the self-healing efficiency was greatly reduced; the agglomerated montmorillonite damaged the compatibility between the shell material and the core material, the flame retardant component was unevenly dispersed, and the limiting oxygen index decreased; at the same time, the agglomeration of the composite component led to poor dispersion of microcapsules in asphalt, which easily formed stress weak points at low temperature, and the flexural strength and strain were significantly reduced.
[0100] Comparative Example 2 used unmodified sodium-based montmorillonite, whose surface hydrophilic groups have poor compatibility with organic waxes. Montmorillonite in the composite component is prone to sedimentation and poor dispersion, resulting in failure of the warm-mix function. The core material has reduced uniformity due to montmorillonite agglomeration, and the self-healing components cannot effectively penetrate cracks, thus reducing the self-healing efficiency. The bonding force between unmodified montmorillonite and shell material is weak, and the flame retardant system of shell material cannot form an effective synergy, resulting in a decrease in the limiting oxygen index. The microcapsules have poor bonding with the asphalt interface, and interface cracking is prone to occur at low temperatures, leading to deterioration of flexural performance.
[0101] Comparative Example 3 uses ungrafted azobenzene nano-silica, which lacks the active release effect of azobenzene groups under ultraviolet light. The release of the shell material to the core material relies solely on passive diffusion. Therefore, the self-healing efficiency of the illuminated group and the unilluminated group is minimal and generally low. The ungrafted nano-silica has weak bonding force with the shell material, resulting in decreased mechanical properties of the shell material, reduced retention rate of flame retardant components, and decreased limiting oxygen index. At the same time, the shell material's encapsulation stability of the core material is insufficient, and premature leakage of the core material leads to poor compatibility with asphalt and impaired low-temperature bending performance.
[0102] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A self-healing, warm-stirring flame-retardant microcapsule, the microcapsule comprising a core material and a shell material; characterized in that, The core material comprises a self-healing component and a warm-mix functional component. The self-healing component is at least one of sulfur, epoxy resin, or recycled asphalt. The warm-mix functional component is an organic wax-montmorillonite composite component, wherein the montmorillonite is modified with a silane coupling agent. The shell material is at least one of ammonium polyphosphate, melamine-formaldehyde resin or nano aluminum hydroxide, and the surface of the shell material is loaded with nano silica particles with surface-grafted azophenyl groups.
2. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 1, characterized in that, The preparation method of the organic wax-montmorillonite composite component includes: Montmorillonite was added to an ethanol solution of silane coupling agent with a mass fraction of 5-8%, and the mass ratio of montmorillonite to silane coupling agent was 10-8:
1. The mixture was heated and stirred, centrifuged, washed, dried, ground and sieved to obtain modified montmorillonite. The organic wax is heated and melted at 120~140℃. Modified montmorillonite is added at a mass ratio of 5~3:1 between the organic wax and the modified montmorillonite. After stirring and reacting, heating is stopped, and stirring is continued until the temperature drops to 60~70℃. After cooling, it is crushed and sieved.
3. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 2, characterized in that, The method of adding modified montmorillonite includes: First, lower the temperature to 100~110℃, then add the modified montmorillonite in 2-6 portions, with an interval of 15~20 minutes between each addition. After each addition, increase the stirring speed by 50~100 r / min. After all the montmorillonite has been added, raise the temperature back to 120~130℃.
4. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 1, characterized in that, The method for preparing the nano-silica with surface grafted azophenyl groups includes: The nano-silica particles were soaked in hydrochloric acid solution, filtered, washed until neutral, and then dried. 4-hydroxyazobenzene and 3-isocyanatepropyltriethoxysilane were added to toluene at a molar ratio of 1:1.1~1.2, and heated and stirred under nitrogen protection to obtain a silane coupling agent derivative containing azophenyl groups. The derivative was cooled and set aside for later use. The pretreated nano-silica particles were added to a mixed solvent of anhydrous ethanol and toluene and ultrasonically dispersed. Then, a silane coupling agent derivative was added, wherein the mass ratio of nano-silica to silane coupling agent derivative was 10~8:
1. The mixture was refluxed and stirred at 80-90℃ for 6-8 hours. The mixture was centrifuged, and the resulting solid was washed with anhydrous ethanol and dried to obtain nano-silica particles with azophenyl groups grafted onto their surface.
5. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 1, characterized in that, The loading of the nano-silica with surface-grafted azophenyl groups is 5-15% of the total mass of the shell material.
6. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 1, characterized in that, The microcapsule particle size is 20~80μm.
7. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 1, characterized in that, The mass ratio of the core material to the shell material is 1:0.6~1.
5.
8. The method for preparing self-healing warm-stirring flame-retardant microcapsules according to any one of claims 1-7, characterized in that, include: The self-healing component and the warm-stirring functional component are melt-mixed at 60~80℃ to obtain a liquid core material; The shell material and nano-silica particles with surface grafted azophenyl groups are dispersed in deionized water to form an aqueous solution. The liquid core material is mixed with an aqueous solution and sheared emulsified to form an oil-in-water emulsion. An initiator was added to the emulsion, the pH was adjusted to 3-5, and the temperature was raised to 70-90℃ for in-situ polymerization for 2-4 hours. After freeze-drying and sieving, microcapsules were obtained.
9. The self-healing, warm-stirring flame-retardant microcapsule as described in claim 8, characterized in that, The initiator is ammonium persulfate or azobisisobutyronitrile, and the amount added is 0.5-2% of the shell material weight.
10. An asphalt mixture, characterized in that, The composition, by weight, includes: 4-6 parts asphalt, 85-92 parts aggregate, 6-8 parts mineral powder, and 0.5-1.0 parts of the microcapsules.
Citation Information
Cited By
Microcapsule packaging repairing agent, anti-icing coating as well as preparation method and application of microcapsule packaging repairing agent and anti-icing coating
CN122103952A